إسهام المرأة في المجال العمراني والثقافي في العصر الأيوبي 570 - 658 هـ / 1174 - 1260 م - عمر، أحمد رضا أحمد (الجمعية العربية للحضارة والفنون الإسلامية, 2016)
The contributions of Muslim women covered many especcts in our Islamic society, women have involved side by side with the man in many areas they are in the battlefields heal and cure the wounded, and in urging jihad against those who wanted to desecrate the soil of the homeland, at the same time she was highly educated in the field of science especially in the Islamic law and what is related to it, or participated in the reconstruction of religious, educational, and service institutions. This precludes the persecution of Islam for women, promoted by biased people against Islam and its people. The Women's influential role in the political side, too, has worked in the Department of Political Affairs on several occasions in the Ayyubid period. In additional to that both the Syria and Egypt have become a center of educational activity for women, where women who did play a role at the field of teaching or learning, although not their appear directly in schools as teachers or students , but many of them have worked in this aspect indirectly, the elders of them or Shekhat or Rawyat of the Hadetih , and be Ancin private schools for boys and for the study of modern jurisprudence and various doctrines, and some of them known for excellence in the art of a certain knowledge of the arts. The role of women to participate in the urban and service area have varied, as well as to their role in the construction of schools have worked hard at building al-zawea and khanqah and Al-hamamat of those enriched by urban relics remain in the Levantine and Egyptian cities. The contribution of women Ayyubid family had not focused in only educational institution building, but they shared by endowments, and their contribution was clear in this area and participated in the promotion of intellectual movement in the Ayyubid period. It will search the institutions built by the princesses Ayoubidy nasty of Akhawatin sisters sultans and their wives and daughters, as well as the ladies of the non- House Ayoubi, we will look as well as talk about the institutions that has been build, and to their culture and their role in the scientific life in that period, if any, and their role as supervisor in the area focuses scientific in that period, where the busy pens and minds of danger Crusader. The study was divided into several sections including: Section 1: a brief on the role of women in Islamic history. Section 2: the political role of women in the Ayyubid period Section 3: Women's culture in the Ayyubid. Section 4: Women's role in the building of religious and service institutions.. Section 5: Women's role in the building of educational institutions.
إن إسهامات المرأة المسلمة غطت مناح عدة في مجتمعنا الإسلامي، فقد شاركت المرأة الرجل في مجالات عديدة، فهي في ساحات القتال تضمد وتداوي الجرحى، وفي الحث على الجهاد ضد من يريد أن يدنس تراب الوطن، وعالمة ومتعلمة في مجال العلم وخاصة العلوم الشرعية وما يتعلق بها، شاركت في تعمير أو بناء المؤسسات الدينية والتعليمية والخدمية، وهذا ينفي صفة اضطهاد الإسلام للمرأة، التي يروج لها المغرضون ضد الإسلام وأهله. وكان للنساء دور مؤثر في الجانب السياسي أيضاً. وكان للمرأة دور متميز في العصر الأيوبي. وكانت الأميرات الأيوبيات متقدمات على غيرهن في شتى المجالات، ومن بينها مجال العلم وإعداد العلماء والخطباء والطلبة والمجاهدين الذين يغذون ساحات المعارك بالرجال المتحمسين للدفاع عن بلاد المسلمين، فضلا عن بنائهم لعديد من المؤسسات الدينية والتعليمية والخدمية، فهؤلاء النسوة شاركن في بناء المساجد والمدارس والمؤسسات الأخرى من أموالهن الخاصة، فكانت لهذه المؤسسات دور ريادي ومتميز في الإعداد الديني والعلمي للطلبة في مختلف المدن الشامية والمصرية، وجاء هذا البحث ليسهم في إلقاء الضوء على دور هؤلاء النسوة في المجال الثقافي وبناء المؤسسات الدينية والتعليمية والخدمية، وسوف يركز البحث على ثقافة المرأة ودورها في الحياة العلمية في العصر الأيوبي والمؤسسات الدينية والخدمية والتعليمية التي قامت ببنائها أميرات البيت الأيوبي من الخواتين أخوات السلاطين وزوجاتهم وبناتهم، فضلا عن السيدات من غير البيت الأيوبي. وتم تقسيم البحث إلى عدة مباحث على النحو التالي: المبحث الأول: نبذة مختصرة عن دور المرأة في التاريخ الإسلامي. المبحث الثاني: دور المرأة السياسي في العصر الأيوبي. المبحث الثالث: ثقافة المرأة في العصر الأيوبي. المبحث الرابع: دور المرأة في بناء المؤسسات الدينية والخدمية. المبحث الخامس: دور المرأة في بناء المؤسسات التعليمية
Keywords: التاريخ الإسلامى; العصر الأيوبى; المرأة; العمارة الإسلامية